ANALISIS KUALITAS PELAYANAN KLAIM PRODUK JASA ASURANSI PT. ASKRINDO PADA SETDA PROVSU - Salwa Hayati Harahap; Zainarti Zainarti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to analyze the quality of insurance product claims services provided by PT ASKRINDO at the Regional Secretariat (SETDA) of North Sumatra Province. This research uses a quantitative descriptive method with data collection techniques through surveys and direct interviews with customers and staff involved in the claims process. The main focus of this research is to evaluate five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and physical evidence (tangible). The research results show that in general, the quality of claims services provided by PT ASKRINDO is quite adequate, but there are several aspects that need to be improved, especially in terms of speed of claim settlement and more effective communication between the company and customers. In addition, analysis of customer satisfaction levels shows that delays in the claim settlement process have a negative impact on customer perceptions of the company